Inhibition of PI3K and calcineurin suppresses chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2)-dependent responses of Th2 lymphocytes to prostaglandin D(2). - Xue, L; Gyles, S; Barrow, A; Pettipher, R (2007)
Interaction of prostaglandin D2 (PGD2) with chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2) triggers chemotaxis and pro-inflammatory cytokine production by Th2 lymphocytes. We have investigated the role of inhibitors of various cell-signalling pathways on the responses of human CRTH2+ CD4+ Th2 cells to PGD2. Phosphatidylinositol 3-kinase (PI3K) and Ca2+/calcineurin/nuclear factor of activated T cells (NFAT) pathways were activated by PGD2 in Th2 cells in a CRTH2-dependent manner. Inhibition of the PI3K pathway with LY294002 significantly reduced both PGD2-induced cell migration and cytokine (interleukin-4, interleukin-5 and interleukin-13) production. The inhibitory effect of LY294002 on cell migration is likely to be related to cytoskeleton reorganization as it showed a similar potency on PGD2-induced actin polymerization. The calcineurin inhibitors, tacrolimus (FK506) and cyclosporin A, had no effect on cell migration but completely blocked both cytokine production and the nuclear translocation of NFATc1 suggesting that Ca2+/calcineurin/NFAT is involved in CRTH2-dependent cytokine production but not chemotaxis. The promotion of NFAT nuclear location by PI3K activation may be mediated by negative regulation of glycogen synthase kinase-3beta (GSK3beta), since the PGD2-stimulated increase in phospho-GSK3beta was down-regulated by LY294002, and inhibition of GSK3beta by SB216763 enhanced PGD2-induced Th2 cytokine production and reversed the inhibitory effect of LY294002. These data suggest that PI3K and Ca2+/calcineurin/NFAT signalling pathways are critically involved in pro-inflammatory responses of Th2 cells to PGD2.